(untitled) (Al-Academy, 2025)
This study examines the aesthetic and expressive values ​​of cosmology through photography and installation art within the context of contemporary art. Art is an effective means of expression for understanding and appreciating astronomy (cosmology), the science that studies the origin and evolution of the universe. This research also highlights a portion of the artistic creativity embodied in photography during the nineteenth and twentieth centuries. This art form emerged at a time when advanced photographic technologies were not available. Artistic practice began with the goal of bringing art-loving audiences closer to the wonders of the universe and enriching the general understanding of cosmic phenomena, with scientific curiosity and the pursuit of discovery being the primary drivers. During this period, a group of artists emerged who sought to explore the hidden beauty behind the clouds—a beauty many fail to see due to the bright lights of the city. This dazzling celestial beauty appears when viewed from quiet locations far from the hustle and bustle of the city, revealing its grandeur and cosmic secrets. This research also explores the influence of scientific discoveries in shaping artistic vision. The research problem is to understand how aesthetic and expressive values ​​in cosmology influence contemporary artworks. The main question addressed by this paper is: "How does astronomy influence artistic creativity and aesthetic expression in contemporary art?" This paper aims to explore the impact of artworks on the general understanding of cosmic phenomena and to examine how art can open new horizons for artistic expression and creativity in astronomy (cosmology). The importance of this research lies in achieving a deeper understanding of cosmic concepts by studying the impact of astronomy on artistic vision and creativity, which contributes to enhancing the interaction between science and art and enriching human knowledge in general. The study relied on a descriptive-analytical approach by reviewing and analyzing a selected group of artworks from a specific group of artists in the fields of photography and installation art during the nineteenth and twentieth centuries. These artists expressed astronomical phenomena using their artistic skills in photography and installation art. These practices enabled them to document minute details that provided a deeper understanding of artistic practices in the field of cosmology. Through a critical analysis of artworks by a group of contemporary artists inspired by cosmology, the research concluded that art plays a pivotal role in enhancing understanding. The scientific study of the universe and the exploration of aesthetic and expressive values ​​in contemporary art, thus providing a qualitative addition to artistic expression and enriching visual language. Furthermore, the study demonstrated that artworks dealing with cosmological themes are capable of broadening audience horizons and encouraging them to reflect more deeply on scientific and philosophical issues related to the universe. These works contribute to creating a connection between science and art, enhancing public awareness of cosmic issues and encouraging further interest and exploration in the field of astronomy.